Neonatal cerebral infarctions: MRI - Küker, W; Möhrle, S; Mader, I; Nägele, T; Schöning, M (2004)
Background: Ischemic stroke in neonates is a rare event presenting clinically with seizures. Due to the immature neonatal brain, diagnosis with most imaging modalities is difficult, but necessary to initiate an anticoagulatory treatment. The purpose of this study was to evaluate the sensitivity of MRI sequences within the first 14 days after birth for a reliable diagnosis of cerebral ischemia. Patients and Methods: Six patients with neonatal stroke presenting as seizures were examined using a standard MRI protocol including DWI and MRA within 3 days after birth. Follow-up examinations were performed in four patients after 5 days (n = 1), 7 days (n = 2) and after 2 weeks (n = 1) for treatment control. Results: 19 infarctions were detected in the six patients with 15 lesions located in the MCA territory and four in the PCA territory. All lesions were visible using DWI, six on T2-weighted images. Whereas in two patients small lesions contralateral to a large stroke were missed on T2, the diagnosis would have been missed altogether in one baby. On follow-up examinations, the visibility of the infarctions had declined using DWI after 5 days and the lesions were invisible after 1 week. 14 days after the stroke, an increased diffusion was detected in the infarcted brain tissue. All lesions were visible on T2-weighted images. Conclusions: Infarcted brain tissue can be detected in neonates using DWI with high sensivity within the first 2 days after stroke and before other sequences are diagnostic. However, the diffusion restriction does not persist beyond 1 week. After 5 days, diagnosis has to rest on T2-weighted images.